Material Management, Information Technology, and Marketing Performance: Implications for Sustainable Business Development in Africa (European Journal of Marketing and Economics, 2018)
One of the primary purposes of every organization is to satisfy the needs of customers. Satisfaction of need based on the premise that sustainable business performance is not in view unless the needs of the customers are satisfied. As a result of economic metamorphosis from pre-industrial era to experience economy, the human factor is considered as the most crucial tool for competitiveness. However, management seems to be placing too much emphasis on human resources at the expense of nonhuman input in production. How do managed efficiently materials affect marketing performance? Does IT facilitate the contributions of material management to business development in Africa? The study adopts the input-throughput-output model to ascertain the effect of material management on marketing performance. The moderating impact of information technology was also explored. A mixture of descriptive and survey research method was adopted. The sample of 400 respondents was drawn from purchasing and supply, store, production, marketing as well as distribution and logistics sections of four different manufacturing firms. Three different hypotheses were developed, and appropriate statistical techniques were employed for the analyses. Most of the functional areas of material management are likely to have positive effects on marketing Performance. There is the tendency that IT will moderate the relationship between material management and business development in Africa. Effective material management facilitated by IT applications plays significant roles in promoting marketing performance and business development in general.
Keywords: Information Technology, Marketing Performance, Material management, Sustainable business